Maximization of a light-wave (LED to photodiode) "Li-Fi" communication range - Muhaimin Mareum Khan (Nanyang Technological University, 2020)
"Li-Fi" is a modality of wireless communication that could be a significant addition to the current ecosystem of Wi-Fi, Bluetooth, and other RF communication systems. For example, by the nature of its electromagnetic carrier frequency in the few 100 THz (due to wavelengths of a few 100nm) it could natively achieve bandwidths far greater than those limited by the crowded spectrum we see today. However, our ability to modulate and detect light waves is still fundamentally limited by our photonic devices and electronics. This project accepts the current limitations of our technology and then builds and maximizes a communication system using light waves as the carrier. This re-thinks the existing IR and UV LED communication systems by investigating different modulation techniques. In so doing, the communication range (shortest to largest distance from the transmitter) is maximized. Communication is achieved using Single Photon Avalanche Diode SPAD detection minimizing distortion of signals from noise generated within the circuit and the external environment. A receiver module is designed that has the lowest noise (and hence highest sensitivity) over a wide dynamic range. Pulse width encoding is used for data modulation. For this project, both the transmitter and receiver module are custom designed from scratch addressing the specific requirements. This project involves the design of Transimpedance Amplifier (TIA), Low Pass Filter (LPF), Low-Noise Amplifier (LNA), Schmitt Trigger, and Diode Driver circuits.